Pengaruh Media Leaflet Terhadap Tingkat Pengetahuan Tentang Metode Kontrasepsi IUD Pada WUS - Lestari, Wa Ode Sri Wati; Rosidi, Indah Yun Diniaty; Musrif, Fitriyanti (Jurnal Keperawatan Florence Nightingale, 2025)
Breast milk is grease emulsion in liquid, lactose and an organic mineral saltthat iscontraceptive methodsare effective  methods for delaying and sparing pregnancy, and stoppingfertility. A preliminary study conducted at Kadolomoko Health Center showed low IUD use due to lack of knowledge about long-term contraceptive methods (LMPs). This emphasizes the importance of education about available contraceptive options. The objective of this study is to determine the effect of counseling on IUD contraceptive methods using leaflet media on the knowledge level of women of childbearing age at Kadolomoko Health Center. This study adopted a design referred to as Experimental with a one group pre testpost test design. In other words, the investigators conducted measurements at two points of time, Pre and Post treatment measures. Normality was tested using Kolmogorov Smirnov and showed the data distributed non-normally. The effect of the IUD contraceptive counseling on leaflet media was evaluated by Wilcoxon test. Before counseling IUD with leaflets, 46% of respondents have sufficient knowledge, 49% have less knowledge, and 5% have good knowledge. Post-counseling, moderate knowledge adoption among the respondents stood at 64.4% while very good knowledge adoption rose to 30,3% and poor knowledge retention fell to 5.3%. IUD counseling using leaflet media has an effect on increasing the level of knowledge of respondents with a p value of 0.000.